ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DALAM PEMECAHAN MASALAH MATEMATIKA MATERI FUNGSI KUADRAT PADA SISWA KELAS IX SMP NEGERI 6 SEMARANG - Sukma Dwi Febriyanti; Rasiman Rasiman; Lilik Ariyanto; Purwanto Purwanto (Jurnal Karya Pendidikan Matematika, 2024)
This research aims to describe junior high school students' mathematical communication skills in Quadratic Function material. This type of research is descriptive qualitative. The subjects were taken from 2 students each with high, medium and low mathematics abilities in class IX of SMP Negeri 6 Semarang 2023/2024. Data collection was carried out using mathematical communication tests, interviews and documentation. The data analysis technique was carried out in 3 stages, namely data reduction, data presentation and drawing conclusions. The data validity checking technique uses the triangulation method. Based on the results of research conducted by researchers, it was found that subjects with high mathematical abilities and subjects with moderate mathematical abilities were able to fulfill all the mathematical communication indicators given in the questions/problem solving. These indicators are 1) Ability to express problem situations in pictures or graphs (drawing) 2) Ability to express problem situations in the form of mathematical models (mathematical expressions) 3) Ability to explain the solution of ideas or situations from an image given in the model mathematics is in the form of mathematical writing (writing). Meanwhile, subjects with low mathematical abilities are unable to fulfill all the mathematical communication indicators given in the questions/problem solving.